Directional Lora Antenna At 433mhz for Point-To-Point Communication - Azhar, Akmal Syafiq; Majid, Huda (Progress in Engineering Application and Technology, 2023)
In modern communication, a number of modulation approaches for long-range wireless sensor networks running at sub-GHz frequencies have recently gained popularity. Various technologies are employed in LoRa use license-free I.S.M. (Industrial, Scientific and Medical) bands of frequencies. Their operating frequencies are in sync at wavelengths of 35 cm or more, resulting in improved performance propagation in both indoor and outdoor environment. These radio waves are very useful in the presence of obstruction because of better penetration and/or diffract more around compared to transmissions at 2.45 GHz, which are extensively used. The I.S.M. band has a wavelength of only 12 cm. There are several unlicensed frequency bands available. The available bands in Europe such as 434 MHz, 868 MHz, 2.45 GHz, and 5.8 GHz. The 434 MHz band has the best propagation qualities of the four, but the wavelength is shorter. Wearable antennas for this frequency tend to be shorter than 70 cm grown quite substantial. The 868 MHz band provides excellent coverage solutions that combine small, wearable antennas with excellent propagation properties. The radiation pattern obtained are in both directional and omnidirectional for meander-line antenna for all the frequencies. The simulated return loss and radiation pattern are used to demonstrate the performance of the antenna.